Two new species of Protolychnis Meyrick, 1925 (Lepidoptera, Lecithoceridae) from the Afrotropical Region, with a world check-list of the genus - Park, Kyu-Tek; Koo, Jun-Mo (Zootaxa, 2020)
Two new species of the genus Protolychnis Meyrick are described: P. petiliella Park, sp. nov. from Uganda and P. bastini Park, sp. nov. from Democratic Republic of Congo and Kenya. Adults, male and female genitalia of both new species are illustrated. A check-list for all known species of the genus is provided.